1995
DOI: 10.1037/0008-400x.27.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Perception de contrôle, désir de contrôle et santé psychologique.

Abstract: ResumeBien qu'il semble evident que la perception de contr61e et le desir de contrdle soient en relation avec la sante psychologique, les conditions particulieres sous lesquelles se manifestent les reactions positives ou negatives demandent a etre precisees. La pr&ente recherche vise a expliciter la relation entre la perception de contrdle, le desir de controle et la sante psychologique. L'examen de la contribution simultanee des deux types de contrdle pour rendre compte des variations du degre de depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…Consistent with its conceptualization as a motivating factor for gaining control, DC is generally positively related to SC (Burger, 1992). However, theory and research suggests that when an individual's perceived level of control does not reach that which they desire, they may experience negative psychological consequences, including anxiety and depression (Braith, McCullough, & Bush, 1988;Burger, 1984Burger, , 1991Burger, , 1992Conway, Vickers, & French, 1992;Evans et al, 1993;Garant & Alain, 1995;Wilkinson & Camove, 1992). One group of researchers has repeatedly examined the relationship between individuals high in DC and low in SC, and their proneness to distress and anxiety (see .…”
Section: Introductionmentioning
confidence: 95%
“…Consistent with its conceptualization as a motivating factor for gaining control, DC is generally positively related to SC (Burger, 1992). However, theory and research suggests that when an individual's perceived level of control does not reach that which they desire, they may experience negative psychological consequences, including anxiety and depression (Braith, McCullough, & Bush, 1988;Burger, 1984Burger, , 1991Burger, , 1992Conway, Vickers, & French, 1992;Evans et al, 1993;Garant & Alain, 1995;Wilkinson & Camove, 1992). One group of researchers has repeatedly examined the relationship between individuals high in DC and low in SC, and their proneness to distress and anxiety (see .…”
Section: Introductionmentioning
confidence: 95%
“…Generally, DC is negatively correlated with trait anxiety (Burger, 1992). However, individuals who have a perceived discrepancy between the level of control they desire and that attained may experience negative psychological consequences, such as anxiety and depression (Baron, Cusumano, Evans, Hodne, & Logan, 2004;Burger, 1984Burger, , 1991Burger, , 1992Conway, Vickers, & French, 1992;Evans et al, 1993;Garant & Alain, 1995;Wilkinson & Camove, 1992). For example, Braith, McCullough and Bush (1988) found that those individuals who experienced increases in anxiety following a relaxation session had higher levels of DC.…”
mentioning
confidence: 99%
“…In other words, desire for control and perceived control have only a small correlation, and they are correlated with the same psychological variables but at different strengths (Auerbach & Pegg, 2002;Burger, 1992;Hatton et al, 1989;Irwin, 2000). Nonetheless, the interaction between desire for control and perceived control can predict various psychological states; for example, high desire for control and low perceived control are related to psychological problems such as anxiety and depression (Garant & Alain, 1995;Logan et al, 1991;Moulding & Kyrios, 2007;Wilkinson & Camove, 1992 ).…”
Section: Two Additional Control-related Conceptsmentioning
confidence: 99%